2023
DOI: 10.1126/science.adf5848
|View full text |Cite
|
Sign up to set email alerts
|

Declining cost of renewables and climate change curb the need for African hydropower expansion

Abstract: Across continental Africa, more than 300 new hydropower projects are under consideration to meet the future energy demand that is expected based on the growing population and increasing energy access. Yet large uncertainties associated with hydroclimatic and socioeconomic changes challenge hydropower planning. In this work, we show that only 40 to 68% of the candidate hydropower capacity in Africa is economically attractive. By analyzing the African energy systems’ development from 2020 to 2050 for different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Imposing a carbon cap increases the cost-competitiveness of hydropower as a source of low-carbon electricity in higher impact scenarios, but when social and environmental exclusions are applied, the reliance on hydropower is very similar to unconstrained emissions scenarios—only 25% of planned or proposed hydropower capacity or 10 GW is necessary and cost-competitive by 2040. This is generally consistent with other studies that explore power system portfolios with varying shares of hydropower capacity and found that solar PV and wind capacity coupled with flexible gas generation are the primary substitutes for hydropower 9 , 11 , 12 , 27 . Studies that have examined optimal technology investments in response to restricting wind and solar PV development due to environmental protections found an overall shift from wind to solar PV 16 , 47 , which we observe for some, but not all, scenarios in Southern Africa.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Imposing a carbon cap increases the cost-competitiveness of hydropower as a source of low-carbon electricity in higher impact scenarios, but when social and environmental exclusions are applied, the reliance on hydropower is very similar to unconstrained emissions scenarios—only 25% of planned or proposed hydropower capacity or 10 GW is necessary and cost-competitive by 2040. This is generally consistent with other studies that explore power system portfolios with varying shares of hydropower capacity and found that solar PV and wind capacity coupled with flexible gas generation are the primary substitutes for hydropower 9 , 11 , 12 , 27 . Studies that have examined optimal technology investments in response to restricting wind and solar PV development due to environmental protections found an overall shift from wind to solar PV 16 , 47 , which we observe for some, but not all, scenarios in Southern Africa.…”
Section: Discussionsupporting
confidence: 91%
“…Studies that have examined optimal technology investments in response to restricting wind and solar PV development due to environmental protections found an overall shift from wind to solar PV 16 , 47 , which we observe for some, but not all, scenarios in Southern Africa. A comparison with basin-level hydropower results from Carlino et al (2023) reveals some notable differences in how much hydropower is deemed cost competitive in Southern Africa 27 . Carlino et al (2023) found that 12–13 GW of hydropower capacity was selected in the Congo basin across all scenarios, whereas our results found only 2–4.8 GW of Congo basin projects to be cost-competitive.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Solar irradiance levels in Africa generally exceed those of other continents, and various regions within SSA offer substantial wind energy potential, with ample land suitable for solar and wind power plants without conflicting with other land uses (Sterl et al 2022). Several countries also boast important hydroelectric power potential, which can play important near-term roles to mitigate solar and wind intermittency (Sterl 2021a(Sterl , 2021b, although recent research suggests hydropower will rapidly cede in importance towards mid-century (Carlino et al 2023).…”
Section: What Energy Transition Means For Scaling Renewable Power Gen...mentioning
confidence: 99%